Ordered Nanostructures of Carbon Nanotube–Polymer Composites from Lyotropic Liquid Crystal Templating. Issue 17 (6th August 2018) - Kasprzak, Christopher R.; Scherzinger, Evan T.; Sarkar, Amrita; Miao, Miranda; Porcincula, Dominique H.; Madriz, Alejandro M.; Pennewell, Zachary M.; Chau, Sophia S.; Fernando, Raymond; Stefik, Morgan; Zhang, Shanju
Abstract: A series of polymer nanocomposites containing single‐walled carbon nanotubes (SWNTs) are prepared from polymerizable quaternary ammonium surfactants using photo‐polymerization and investigated by means of polarized optical microscopy, small‐angle X‐ray scattering, and rheological measurements. The surfactant monomers with various alkyl chains of nonpolar tails form lyotropic liquid crystalline (LLC) mesophases in aqueous medium with hexagonal packing of cylindrical micelles. The physical adsorption of nonpolar tails of surfactants on the surface of SWNTs results in de‐bundled nanotubes. The LLC phase diagram is investigated as functions of alkyl chain length, concentration, temperature, and SWNTs. As such, addition of SWNTs does not change the hexagonal mesophases but enhances the order–disorder transition temperatures and alters the rheological behaviors. After photo‐polymerization, the microstructures of hexagonal packing are changed while addition of SWNTs does not disrupt the resulting microstructures. The polymerized composites are consistent with both lamellar and gyroid nanostructures and a possible model is proposed to interpret the observed phenomenon. Under the shear flow, the defect‐free monodomain structures are obtained in the LLC phase and subsequently locked in the solid film after polymerization. Abstract : A series of polymer single‐walled carbon nanotubes nanocomposites with ordered nanostructures are prepared from polymerizable liquid crystalline surfactants using photopolymerization. Lyotropic liquid crystalline surfactants serve as dispersants and templates to exfoliate and orient nanotubes into various ordered materials.